Higher Abundance of Marine Predators and Changes in Fishers' Behavior Following Spatial Protection within the World's Biggest Shark Fishery - Jaiteh, Vanessa F.; Lindfield, Steve J.; Mangubhai, Sangeeta; Warren, Carol; Fitzpatrick, Ben; Loneragan, Neil R. (Frontiers in Marine Science, 2016)
Fisheries are complex social-ecological systems, where managers struggle to balance the socio-economic interests of fishing communities with the biology and ecology of fisheries species. Spatial closures are a popular measure to address conservation and fisheries management goals, including the protection of shark populations. However, very little research has been published on the effectiveness of shark-specific closures to protect sharks, or their impacts on fisher behavior. Situated within the global center of tropical marine biodiversity, Indonesia’s shark fishery contributes more to the international shark fin trade than any other nation. Here we evaluate the effect of shark-specific closures on sharks and other species of interest, as well as shark fishers’ responses to losing access to their former fishing grounds. We assessed shark diversity and abundance in an open access zone (OAZ) and two No-Take Zones (NTZs) of a Marine Protected Area within the recently established shark sanctuary in Raja Ampat, Indonesia, where sharks have high monetary value as a tourism attraction. Shark abundance was significantly higher in the privately managed NTZs than in the OAZ. Across all management zones, neither zone size, depth nor reef complexity explained variations in shark abundance, suggesting that governance is the main driver of successful shark conservation areas. These trends were also reflected in species targeted by small-scale reef fisheries, including snappers, emperor, groupers, tunas, mackerels, and large-bodied wrasse and parrotfish. Interviews with shark fishers who lost access to their primary fishing grounds when the shark sanctuary was established showed that while most fishers (88%) knew that sharks were protected in Raja Ampat, many were unsure about the purpose of the sanctuary. Few fishers felt that the agencies implementing fishing bans understood their livelihood needs. We found that shark fishers adapted to the loss of former fishing grounds by shifting fishing effort to other locations or diversifying their livelihoods, including illegal petrol transport. While conserving sharks for tourism can be effective, it may inadvertently result in displacing fishing effort to unprotected regions. We propose that effective shark conservation in Indonesia will need to combine strategic spatial protection with efforts to support livelihood security and diversification.